The relationship between employees job stress and job performance among staff at Sarawak Timber Industry Development Corporation (STIDC) / Nur Zahariah Haji Maimon - Haji Maimon, Nur Zahariah
This study is explore the relationship between employee job stress and employee job performance at Sarawak Timber Industry Development Corporation. The framework of this research was adapted based on Karasek's Job Demands-Control (JDC) Model. The design used for this study was correlational research. Convenience sampling was used to collect data. 10-point Likert Scale items were used in this study. Out of 100 support staff participated in this study, only 66 sets questionnaire were returned and considered usable. The result indicates that workloads, time pressure, skill discretion, and decision authority had positive and significant relationship with job performance. For workload, majority of the employees at STIDC were capable of managing heavy workload and they have been working at the company for more than 10 years. Due to that, they already had adapted fast-paced workload.